2017
DOI: 10.1088/2053-1583/aa65c2
|View full text |Cite|
|
Sign up to set email alerts
|

Nano-bio compatibility of PEGylated reduced graphene oxide on mesenchymal stem cells

Abstract: Graphene, with its unique physico-chemical properties, has found widespread biomedical application. It is used as a carrier for drug or gene delivery, photothermal therapy, bioimaging, in antibacterial agents and for the development of biosensors. Besides this, graphene has the scope to be used for wound healing, tissue engineering and regenerative medicine. In the present study, polyethylene-glycol-(PEG)ylated reduced graphene oxide (PrGO) was synthesized, characterized, and its interaction with mouse bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…Besides GO, the effect of PEGfunctionalized rGO (PrGO) was also evaluated on MSCs. 54 PrGO was neither toxic nor impaired the differentiation potential of MSCs, which confirmed the prospect of PEGylated graphene derivatives in tissue engineering.…”
Section: Interaction With Stem Cellssupporting
confidence: 57%
“…Besides GO, the effect of PEGfunctionalized rGO (PrGO) was also evaluated on MSCs. 54 PrGO was neither toxic nor impaired the differentiation potential of MSCs, which confirmed the prospect of PEGylated graphene derivatives in tissue engineering.…”
Section: Interaction With Stem Cellssupporting
confidence: 57%
“…Such adsorbed protein layer is usually termed as the protein corona. In a recent work carried out by Syama et al [ 120 ], rGO-PEG (PrGO) was found to have no toxicity in mouse bone marrow mesenchymal stem cells (MSCs), and it did not appear to impair their differentiation. PrGO was prepared by reducing GO-PEG with sodium borohydride.…”
Section: Cell Viability and Toxicitymentioning
confidence: 99%
“…Another GO derivative, reduced graphene oxide (rGO), with partial or total oxygen depletion, has a more restored π-conjugated structure [ 11 ], rendering this nanomaterial amenable for optical biosensor development [ 12 , 13 , 14 ]. For prospective biosensors capable of direct cell measurement, rGO functionalization using polythiophene- g -poly (ethylene glycol) with lateral amino groups (PEG-NH 2 ) has been shown to not impair the osteogenic differentiation potential of murine mesenchymal multipotent cells [ 15 ]. Functionalizing rGO with PEG-NH 2 helped improve the solubility and stability of rGO suspensions in more complex medium solutions such as those used to support cell growth.…”
Section: Introductionmentioning
confidence: 99%